The Influence of Aspect Ratio and Orientation to Scattering Properties of Ellipsoid Ice Particles - Jinhu Wang; Junxiang Ge; Ming Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The influence of aspect ratio and orientation to scattering properties of ellipsoid ice particles at 94GHz is studied by Discrete-Dipole Approximation (DDA) method. Absorption efficiency, scattering efficiency, asymmetry factor and backscattering efficiency are computed with aspect ratios vary from 0.2 to 1.0, whose size parameter range are selected from 0 to 5. It is found that the values of scattering properties are increasing if the particle size increases, but if the size is larger than the limit value, oscillation occur, and the oscillation phenomenon will be smoothed by random orientation compared with that of horizontal orientation because scattering properties computed by random orientation method have more average frequency than that of horizontal orientation. In non-oscillating region, the scattering efficiency is larger than the absorption efficiency due to small imaginary part of the complex refractive of ice at 94 GHz, and scattering properties increase if the aspect ratio increases with the same size parameter but this feature is apparent only in the case of horizontal orientation. The asymmetric degree of forward scattering and backscattering increases when particle size increases when size parameter of particle is not exceeding 1.5.